Microbiological Profile of Meat from Pekin Ducks During Refrigerated Storage in Air and Vacuum - R Hulankova; I Svobodova (Brazilian Journal of Poultry Science, 2024)
ABSTRACT This study investigates the dynamics of spoilage microflora in duck meat packed in vacuum and air during 9 days of storage. In total, 72 duck carcasses were used in the study. Samples of meat (breasts and thighs, with or without skin) were analysed on days 1, 3, 6 and 9 after packaging in two different atmospheres, at a storage temperature of 3°C ± 1°C. Enterobacteriaceae, coliform bacteria, and E. coli, Total Viable Count, psychrotrophic microorganisms, Lactic Acid Bacteria, Pseudomonas spp. counts, and Brochothrix thermosphacta were determined. As expected, the type of sample and storage length had the greatest influence on microbiological quality (p<0.001). Lower significance (p<0.01) was observed for the place of sampling factor - i.e. duck breast or thigh. As expected, better microbiological parameters were achieved with vacuum-packed samples. The pH value increased during storage, but the increase was minimal for the vacuum-packed samples. In all the microbiological parameters monitored, the best results at the end of storage were obtained for duck breast muscles packed in vacuum.